Prospects for Gampong-Based Halal Tourism Development in Aceh: An ANP Study - Pasarela, Husni; Sukiman, Sukiman; Batubara, Chuzaimah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
Halal tourism is increasingly recognized as a strategic sector in the global travel industry, particularly in regions that integrate Islamic values with community-based development. In Aceh Province, where Islamic law is formally applied, the potential of gampong (village)-based halal tourism is substantial but faces persistent structural challenges. This study aims to identify key obstacles to its development and provide policy insights for sustainable growth. A mixed-methods case study was conducted through literature review and in-depth interviews with stakeholders, including the Aceh Tourism Office, DPR Aceh, MPU, academics, business actors, and local communities. The Analytic Network Process (ANP) was employed to prioritize issues using pairwise comparison questionnaires. The findings indicate three major barriers. First, from the regulatory aspect, the absence of standardized halal tourism guidelines is the most critical challenge (33.27%). Second, under destination factors, inadequate infrastructure and accessibility represent the dominant issue (33.71%). Third, on the social side, limited government support, weak promotion, and neglected historical sites remain significant obstacles (23.99%). These results highlight the urgent need for cross-sector collaboration, improved infrastructure, and inclusive promotional strategies. Strengthening local stakeholder capacity is essential to accelerate sustainable halal tourism and support the Islamic economy in rural Aceh. Abstrak Prospek Wisata Halal Berbasis Gampong Di Aceh: Suatu Kajian dengan Metode ANP. Wisata halal semakin menjadi sektor strategis dalam industri pariwisata global, terutama di wilayah yang memadukan nilai Islam dengan pembangunan berbasis masyarakat. Di Provinsi Aceh, yang secara formal menerapkan syariat Islam, potensi wisata halal berbasis gampong (desa) sangat besar, tetapi dalam dalam implementasinya masih menghadapi berbagai tantangan. Penelitian ini bertujuan mengidentifikasi tantangan utama dalam pengembangan wisata halal berbasis gampong di Aceh dan memberikan masukan kebijakan untuk pertumbuhan berkelanjutan. Penelitian ini menggunakan pendekatan mixed methods dengan desain studi kasus, melalui studi literatur dan wawancara mendalam dengan pemangku kepentingan seperti Dinas Pariwisata Aceh, DPR Aceh, MPU, akademisi, pelaku usaha, dan masyarakat lokal. Metode Analytic Network Process (ANP) digunakan untuk memprioritaskan masalah melalui kuesioner perbandingan berpasangan. Hasil penelitian menunjukkan adanya tiga hambatan utama. Pertama, pada aspek regulasi, ketiadaan standar baku wisata halal menjadi masalah paling krusial (33,27%). Kedua, pada aspek destinasi, infrastruktur dan aksesibilitas yang belum memadai merupakan tantangan utama (33,71%). Ketiga, pada aspek sosial, minimnya dukungan pemerintah, lemahnya promosi, serta terbengkalainya situs sejarah menjadi hambatan signifikan (23,99%). Implikasi penelitian menekankan pentingnya kolaborasi lintas sektor, peningkatan infrastruktur, dan strategi promosi inklusif. Penguatan kapasitas masyarakat lokal sangat diperlukan untuk mempercepat pengembangan wisata halal berkelanjutan dan mendukung ekonomi syariah di pedesaan Aceh